REPRESENTASI NILAI SOSIAL DAN NILAI MORAL DALAM NOVEL PIANO KOTAK KACA KARYA AGNES JESSICA - Adriani Adriani; Darlisa Muhammad; Nuzul Tenriana (Jurnal Bilingual, 2022)
Literature is a form of one's ideas through a view of the social environment around them by using beautiful language. Literature is present as the author's contemplation of existing phenomena. The Piano in a Glass Box is a type of prose literary work that represents various phenomena and values in social life. The values contained and often appear in the novel Piano di Kaca Kaca are moral values and social values. Social value is something that becomes a measure and assessment of the appropriateness of an attitude aimed at social life. The social values contained in the novel Piano in the Glass Box by Agnes Jessica are the attitude of helping each other, caring, compassion, responsibility, and cooperation. While the moral values conveyed in literary works are basically the values conveyed by the author in order to educate humans in all aspects or issues of life and life so that humans can regulate their behavior to become good human beings. The moral values contained in the novel Piano in a Glass Box are about how real social life is. In moral values there are types and forms of morals which include (1) human relations with oneself; (2) Human relations with other humans in the social sphere including their relationship with the natural environment; (3) Human relationship with God. Besides that, in moral values there are basic moral principles which include (1) the principle of goodness; (2) The principle of justice; (3) The principle of self-respect. In moral values there are also moral personality attitudes which include honesty, authentic values, the value of willingness to be responsible, moral independence, moral courage, and humility.